Use of chlorophyll meter sufficiency indices for nitrogen management of irrigated rice in Asia - Hussain, F.; Bronson, K.F.; Singh, Yadvinder; Singh, Bijay; Peng, S. (Wiley, 2000)
Low N fertilizer recovery efficiency (RE) remains a problem in rice (Oryza sativa L.) production in Asia. The chlorophyll meter has been shown to identify when rice is in need of a N top‐dressing, that if applied would result in greater agronomic efficiency (AE) of N fertilizer than commonly practiced, pre‐set timing schemes. Critical chlorophyll meter readings have been used to match N top‐dressing with plant demand for the cultivar IR72, but fixed critical readings may not apply to multiple cultivars and locations. Our objective was to test the approach of using sufficiency indices, calculated from chlorophyll meter readings relative to well‐fertilized reference plots, with several rice cultivars in the Philippines and in India by comparing with local fixed N timing recommendations. Chlorophyll meter readings were significantly affected by N management practice, cultivar, and time of application at both locations. Similar rice yields were produced with chlorophyll meter sufficiency indices compared with the fixed N timing treatment with 30 kg less N ha−1 in the wet season in all cultivars at both locations. Compared with fixed‐timing, 45 kg less N ha−1 was used with the chlorophyll meter in the Philippines dry season without a yield reduction in three of four cultivars. In conclusion, chlorophyll meter sufficiency indices identified when several rice cultivars at two locations needed a N top‐dressing, which resulted in greater AE of N fertilizer than local, pre‐set splits.